Life monitoring : a proposal for product end of life management - Felipe Rudiuk Miglorância (2011)
This work develops an aircraft end of life management framework applicable to an executive airplane manufacturer. Usually, end of life operations are outsourced and the original airplane manufacturers do not get directly involved in whatever decisions and tasks are done in this field. However, after considering the possibility of managing the aircraft';s end of life through the manufacturer';s customer support department, a new approach emerges for managing reusable systems and making disposal of non reusable systems and carcasses. It tends to elevate end of life operations from an obligation to become an enhancement in customer satisfaction and possibly revenue, somewhat similar to what happened to maintenance procedures in the recent past of the aeronautical sector. For the development of the proposed system (approach), a process mapping is made for better understanding of operations needed to be done and a strategic approach to these operations is reached, leading to a new maintenance program called Life Monitoring. Therefore, a linkage among environmental management, customer support and aircraft salvaging is established in a way that both the company and the customer be benefited. Although the program is elaborated and applied in a simulated case, the results may be transferred to the manufacturing of any real executive aircraft and, less directly, any product. .